Metal fire extinguishing agent and preparation method and application thereof

CN118807167BActive Publication Date: 2026-10-09SOUTHWEAT UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410793632.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2026-10-09
Estimated Expiration
2044-06-19

AI Technical Summary

Technical Problem

[0004]虽然D类干粉灭火剂有应用市场,但是由于工程应用研究深度不够,没获得必要的系统设计数据

Benefits of technology

[0016] (1) The metal fire extinguishing agent provided by the present invention uses modified nano-TiO2 as the core, which is conducive to the coating of liquid metal. Liquid metal has excellent heat transfer properties, which is conducive to the transfer of external heat. Moreover, coating the outer surface of nano-TiO2 can prevent the agglomeration of nanomaterials, so that the extinguishing agent has good dispersibility. When nano-TiO2 changes from anatase to rutile, it will undergo crystallization and heat absorption. During fire extinguishing, liquid metal transfers external heat to anatase nano-TiO2. Anatase nano-TiO2 absorbs heat and changes its crystal form. The two work together to reduce the temperature of the burning metal below the ignition point, thereby extinguishing the fire. The metal fire extinguishing agent provided by the present invention has a very good fire extinguishing effect on Class D metal fires.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118807167B_ABST
    Figure CN118807167B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of fire extinguishing materials, in particular to a metal fire extinguishing agent, a preparation method and application thereof. The metal fire extinguishing agent comprises modified nano-TiO2 and liquid metal coated at least partially on the outer surface of the modified nano-TiO2; the modified nano-TiO2 comprises nano-TiO2 and a surface modifier coated at least partially on the outer surface of the nano-TiO2, and the crystal form of the nano-TiO2 is anatase. The metal fire extinguishing agent provided by the present application can achieve the effect of extinguishing D-class metal fire through nano-TiO2 crystal transformation endothermic and excellent heat transfer properties of the liquid metal, and has excellent extinguishing effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fire extinguishing materials technology, and more specifically, to a metal fire extinguishing agent, its preparation method, and its application. Background Technology

[0002] With the advancement of technology, metals such as potassium, sodium, aluminum, magnesium, and zinc are receiving increasing attention, and their applications are constantly expanding. These metals readily react violently with other substances, causing combustion or explosions that are difficult to extinguish and highly dangerous. The combustion process also releases toxic substances, placing high demands on firefighters and equipment. Frequent metal fires can lead to serious casualties and economic losses.

[0003] Currently, there are good solutions for extinguishing Class A, B, and C fires, but there are no good solutions for extinguishing Class D fires (such as fires caused by the combustion of metals like potassium, sodium, and magnesium). Because metal fires are characterized by high combustion temperatures and severe damage, conventional general-purpose extinguishing agents cannot be used. Class D fires are among the most difficult to extinguish, making research on extinguishing Class D fires extremely important.

[0004] Although Class D dry powder fire extinguishing agents have an application market, insufficient in-depth research into engineering applications has resulted in a lack of necessary system design data. Class B and C dry powder fire extinguishing systems are more mature in engineering applications; Class D dry powder fire extinguishing systems are technically less mature. With the development of domestic industry, researching efficient methods for extinguishing fires on metal surfaces has become a pressing priority.

[0005] In view of this, the present invention is hereby proposed. Summary of the Invention

[0006] The primary objective of this invention is to provide a metal fire extinguishing agent, which has a core-shell structure with modified nano-TiO2 as the core and liquid metal as the outer shell. The extinguishing agent achieves the fire extinguishing effect for Class D metal fires through the heat absorption of nano-TiO2 crystallization and the excellent heat transfer properties of liquid metal.

[0007] The second objective of this invention is to provide a method for preparing the metal fire extinguishing agent as described above. This method has a simple process flow, mild and easy-to-control reaction conditions, low production cost, and the extinguishing agent prepared has a good extinguishing effect on metal fires.

[0008] The third objective of this invention is to provide an application of the metal fire extinguishing agent described above in extinguishing metal fires.

[0009] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted:

[0010] A metal fire extinguishing agent includes modified nano-TiO2 and liquid metal at least partially coated on the outer surface of the modified nano-TiO2;

[0011] The modified nano-TiO2 includes nano-TiO2 and a surface modifier that at least partially coats the outer surface of the nano-TiO2, wherein the nano-TiO2 has anatase crystal form.

[0012] A method for preparing a metal fire extinguishing agent as described above includes the following steps:

[0013] The metal fire extinguishing agent is obtained by coating liquid metal onto the surface of modified nano-TiO2.

[0014] The application of a metal fire extinguishing agent as described above in extinguishing metal fires.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0016] (1) The metal fire extinguishing agent provided by the present invention uses modified nano-TiO2 as the core, which is conducive to the coating of liquid metal. Liquid metal has excellent heat transfer properties, which is conducive to the transfer of external heat. Moreover, coating the outer surface of nano-TiO2 can prevent the agglomeration of nanomaterials, so that the extinguishing agent has good dispersibility. When nano-TiO2 changes from anatase to rutile, it will undergo crystallization and heat absorption. During fire extinguishing, liquid metal transfers external heat to anatase nano-TiO2. Anatase nano-TiO2 absorbs heat and changes its crystal form. The two work together to reduce the temperature of the burning metal below the ignition point, thereby extinguishing the fire. The metal fire extinguishing agent provided by the present invention has a very good fire extinguishing effect on Class D metal fires.

[0017] (2) The process of the present invention is simple, the reaction conditions are mild and easy to control, and the manufacturing cost is low. It utilizes the heat absorption of nano-TiO2 crystal transformation and the excellent heat transfer properties of liquid metal for fire extinguishing, providing a new idea for the design and research of fire extinguishing agents for Class D metal fires. Attached Figure Description

[0018] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0019] Figure 1 This is a schematic diagram of the structure of a metal fire extinguishing agent provided in an embodiment of the present invention;

[0020] Figure 2This is a diagram illustrating the fire extinguishing effect of the metal fire extinguishing agent prepared in Example 5 of the present invention.

[0021] Figure label:

[0022] 1-Liquid metal; 2-Surface modifier; 3-Nano TiO2. Detailed Implementation

[0023] The technical solution of the present invention will be clearly and completely described below with reference to the accompanying drawings and specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0024] like Figure 1 The first aspect of the present invention provides a metal fire extinguishing agent, comprising modified nano-TiO2 and liquid metal 1 at least partially coated on the outer surface of the modified nano-TiO2;

[0025] The modified nano-TiO2 includes nano-TiO2 3 and a surface modifier 2 that at least partially coats the outer surface of the nano-TiO2 3, wherein the nano-TiO2 3 has anatase crystal form.

[0026] The metal fire extinguishing agent provided by this invention has a core-shell structure with modified nano-TiO2 as the core and liquid metal as the outer shell. Liquid metal has good thermal conductivity, and coating the modified nano-TiO2 to form a core-shell structure can improve the heat absorption of nano-TiO2. Furthermore, nanomaterials are easy to agglomerate, and the core-shell structure of the extinguishing agent has good dispersibility. This invention mainly utilizes the heat absorption of nano-TiO2 through crystal transformation (from anatase to rutile) and the excellent heat transfer properties of liquid metal to achieve the effect of extinguishing Class D metal fires. During fire extinguishing, external heat is transferred to anatase nano-TiO2 through liquid metal. Nano-TiO2 absorbs the heat transferred by liquid metal and transforms into crystals, thereby reducing the temperature of the burning metal below the ignition point and achieving fire extinguishing.

[0027] In some specific embodiments of the present invention, the liquid metal includes an alloy of one or more of gallium, indium, and tin.

[0028] In some preferred embodiments of the present invention, the liquid metal includes gallium-based liquid metals, such as metallic gallium, gallium-indium alloys, gallium-indium-tin alloys, etc. Gallium-based liquid metals have very low toxicity and very low vapor pressure at room temperature, making them extremely safe. Moreover, compared with common thermal interface materials, they have higher thermal conductivity and lower interfacial contact thermal resistance. The thermal conductivity of gallium-based liquid metal thermal interface materials is far higher than that of most commercially available thermal greases, exhibiting excellent thermal conductivity, which is beneficial for transferring external heat to nano-TiO2.

[0029] In some specific embodiments of the present invention, the surface modifier includes oleic acid and / or F2311 (an equimolar copolymer of vinylidene fluoride and trifluorochloroethylene). The purpose of using oleic acid and / or F2311 to modify nano-TiO2 is to allow liquid metal to better coat nano-TiO2, thereby improving the fire extinguishing effect.

[0030] In some preferred embodiments of the present invention, the surface modifier is oleic acid, and the fire extinguishing agent prepared by using oleic acid-modified nano-TiO2 has a better fire extinguishing effect on metal fires.

[0031] In some specific embodiments of the present invention, the particle size of the nano-TiO2 is 20-500nm, for example, any one value or a range of any two values ​​among 20nm, 50nm, 100nm, 200nm, 300nm, 400nm, and 500nm.

[0032] If the particle size is too small, it is difficult to coat the liquid metal; if the particle size is too large, the prepared powder is difficult to spray out. Therefore, it is necessary to reasonably control the particle size of nano TiO2.

[0033] A second aspect of the present invention provides a method for preparing a metal fire extinguishing agent as described in any of the foregoing embodiments, comprising the following steps:

[0034] The metal fire extinguishing agent is obtained by coating liquid metal onto the surface of modified nano-TiO2.

[0035] The method of this invention has a simple process flow, mild and easy-to-control reaction conditions, and low manufacturing cost. It utilizes the heat absorption of nano-TiO2 crystallization and the excellent heat transfer properties of liquid metal for fire extinguishing, providing a new approach for the design and research of extinguishing agents for Class D metal fires.

[0036] In some specific embodiments of the present invention, the method of coating liquid metal onto the surface of modified nano-TiO2 includes the following steps:

[0037] The modified nano-TiO2 is dispersed in a first solvent, the liquid metal is added, and after mixing evenly, it is dried to obtain the final product.

[0038] In some specific embodiments of the present invention, when preparing the fire extinguishing agent, the amount of liquid metal used accounts for 1%-10% of the mass percentage of the modified nano-TiO2 used, for example, any one value or a range of any two values ​​from 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%.

[0039] Excessive use of liquid metal can lead to excessively large core-shell particles, while insufficient use can result in uneven coating, both of which can affect the extinguishing performance of the fire extinguishing agent. Therefore, it is necessary to reasonably control the ratio of liquid metal to modified nano-TiO2 in order to achieve better fire extinguishing effect.

[0040] In some specific embodiments of the present invention, the first solvent includes ethanol, preferably anhydrous ethanol.

[0041] In some specific embodiments of the present invention, after the liquid metal is added, the mixing method includes stirring and / or ultrasonic mixing.

[0042] In some specific embodiments of the present invention, the liquid metal is a gallium-based liquid metal, preferably a gallium indium tin alloy.

[0043] In some specific embodiments of the present invention, the mass ratio of gallium, indium and tin in the gallium-indium-tin alloy is 62.5-68:21.5-22:10-16, for example 62.5:21.5:16, 68:22:10, etc.

[0044] In some specific embodiments of the present invention, the preparation method of the gallium indium tin alloy includes the following steps:

[0045] Gallium, indium, and tin are placed in a reactor in a specific ratio, heated and stirred to melt and mix them, and then an alkaline solution is added to wash away the metal oxides such as gallium oxide, indium oxide, and tin oxide on the surface of the liquid metal. The liquid metal is then obtained by sonication.

[0046] In some specific embodiments of the present invention, when preparing gallium indium tin alloy, a water bath heating method is used, and the heating temperature is 60-70°C.

[0047] In some specific embodiments of the present invention, the alkaline solution includes at least one of lithium hydroxide solution, sodium hydroxide solution, potassium hydroxide solution, rubidium hydroxide solution, and cesium hydroxide solution.

[0048] In some specific embodiments of the present invention, the concentration of the alkaline solution is 0.5-5 mol / L.

[0049] In some specific embodiments of the present invention, the preparation method of the modified nano-TiO2 includes the following steps:

[0050] Nano-TiO2 and surface modifier are dispersed in a second solvent. After the reaction is complete, a TiO2-modifier dispersion is obtained. The TiO2-modifier dispersion is then added dropwise into a non-solvent while stirring. After standing, filtering, and drying, modified nano-TiO2 is obtained.

[0051] In some specific embodiments of the present invention, the method of dispersing nano-TiO2 and surface modifiers into a second solvent includes ultrasonic dispersion and / or stirring dispersion.

[0052] In some specific embodiments of the present invention, the preparation method of TiO2-modifier dispersion includes the following steps: first, nano-TiO2 is added to a second solvent, ultrasonically and stirred to disperse, then a surface modifier is added, and the mixture is stirred to react, thus obtaining the desired product.

[0053] In some other specific embodiments of the present invention, the preparation method of TiO2-modifier dispersion includes the following steps: first, the surface modifier is stirred and dispersed in a second solvent, then nano-TiO2 is added, ultrasonically dispersed, and stirred to react, thus obtaining the desired product.

[0054] In some specific embodiments of the present invention, when the surface modifier is oleic acid, the second solvent is cyclohexane and / or n-hexane; when the surface modifier is F2311, the second solvent is DMF (N,N-dimethylformamide) and / or DMAc (N,N-dimethylacetamide).

[0055] In some specific embodiments of the present invention, when preparing modified nano-TiO2, the amount of surface modifier used accounts for 1%-5% of the mass percentage of nano-TiO2, for example, any one value or a range of any two values ​​from 1%, 2%, 3%, 4%, to 5%.

[0056] If the ratio of surface modifier to nano TiO2 is too low, the modification of nano TiO2 will be uneven; if the ratio is too high, there will be too much modifier residue, which will be difficult to separate and remove later, both of which will affect the performance of the fire extinguishing agent.

[0057] In some specific embodiments of the present invention, when preparing the TiO2-modifier dispersion, the reaction temperature is 50-60℃, for example, any one value or a range of any two values ​​among 50℃, 52℃, 55℃, 58℃, and 60℃; the reaction time is 1-3h, for example, any one value or a range of any two values ​​among 1h, 2h, and 3h; the preferred heating method for the reaction process is water bath heating.

[0058] In some specific embodiments of the present invention, the non-solvent includes ethanol and / or methanol, and the ethanol used is preferably anhydrous ethanol.

[0059] The purpose of adding TiO2-modifier dispersion to a non-solvent is to use a solvent-non-solvent method to coat the surface modifier onto the surface of nano-TiO2 for modification.

[0060] In some specific embodiments of the present invention, the volume ratio of the second solvent to the non-solvent is 1:2 to 1:30, for example, any one value or a range of any two values ​​from 1:2, 1:5, 1:10, 1:12, 1:15, 1:20, 1:25, 1:30.

[0061] In some specific embodiments of the present invention, the rotation speed when the TiO2-modifier dispersion is dropped into the non-solvent is 400-1200 rpm, for example, any one value or a range of any two values ​​among 400 rpm, 600 rpm, 800 rpm, 1000 rpm, and 1200 rpm.

[0062] The application of the metal fire extinguishing agent as described in any one of the foregoing embodiments, or the metal fire extinguishing agent prepared by the preparation method of the metal fire extinguishing agent as described in any one of the foregoing embodiments, in extinguishing metal fires.

[0063] The following detailed description of some embodiments of the present invention is provided in conjunction with specific examples. Unless otherwise specified, all raw materials used in the embodiments are commercially available.

[0064] Example 1

[0065] Preparation of liquid metal: First, weigh Ga / In / Sn in a ratio of 68:22:10. Mix 6.7962g of Ga and 2.2078g of In at 600rpm for 20 minutes under a 70℃ water bath heating condition. Then add 0.9976g of Sn and continue mixing at 600rpm for 40 minutes under a 70℃ water bath heating condition. Next, prepare a 1mol / L NaOH solution and add 10mL of NaOH solution to the above metal mixture. Sonicate at 200W for 5 minutes to obtain liquid metal.

[0066] Modification of nano-TiO2: First, 0.5002g of nano-TiO2 with a particle size of 200nm was added to 15mL of cyclohexane and ultrasonically dispersed for 10 minutes at 200W and stirred at 600rpm for 10 minutes to ensure uniform dispersion. Then, 0.0050g of oleic acid (1wt% of nano-TiO2) was added, and the mixture was stirred at 600rpm for 2 hours in a 60℃ water bath. Finally, 150mL of anhydrous ethanol was added dropwise while stirring at 400rpm to ensure that the volume ratio of cyclohexane to anhydrous ethanol was 1:10. The mixture was allowed to stand, filtered, and allowed to evaporate naturally to obtain the modified nano-TiO2.

[0067] Preparation of metal fire extinguishing agent: 0.4621g of modified nano-TiO2 was added to 20mL of anhydrous ethanol and stirred at 600rpm for 20 minutes. Then, 0.0047g of liquid metal was added to ensure that the mass percentage of liquid metal in modified nano-TiO2 was 1%. The mixture was stirred at 600rpm for 2 hours, sonicated at 200W for 5 minutes each time, and dried to obtain a metal fire extinguishing agent with a modified nano-TiO2@liquid metal core-shell structure.

[0068] Example 2

[0069] Preparation of liquid metal: First, weigh Ga / In / Sn in a ratio of 68:22:10. Mix 6.7962g of Ga and 2.2078g of In at 600rpm for 20 minutes under a 70℃ water bath heating condition. Then add 0.9976g of Sn and continue mixing at 600rpm for 40 minutes under a 70℃ water bath heating condition. Next, prepare a 1mol / L NaOH solution and add about 10mL of NaOH solution to the above metal mixture. Sonicate at 200W for 5 minutes to obtain liquid metal.

[0070] Modification of nano-TiO2: First, 0.4997g of nano-TiO2 with a particle size of 200nm was added to 15mL of cyclohexane and ultrasonically dispersed for 10 minutes at 200W and stirred at 600rpm for 10 minutes to ensure uniform dispersion. Then, 0.0047g of oleic acid (1wt% of nano-TiO2) was added, and the mixture was stirred at 600rpm for 2 hours in a 60℃ water bath. Finally, 150mL of anhydrous ethanol was added dropwise while stirring at 400rpm to ensure that the volume ratio of cyclohexane to anhydrous ethanol was 1:10. The mixture was allowed to stand, filtered, and allowed to evaporate naturally to obtain the modified nano-TiO2.

[0071] Preparation of metal fire extinguishing agent: 0.4592g of modified nano-TiO2 was added to 20mL of anhydrous ethanol and stirred at 600rpm for 20 minutes. Then, 0.0142g of liquid metal was added to ensure that the mass percentage of liquid metal in modified nano-TiO2 was 3%. The mixture was stirred at 600rpm for 2 hours, accompanied by 200W sonication three times for 5 minutes each time. After drying, a metal fire extinguishing agent with a modified nano-TiO2@liquid metal core-shell structure was obtained.

[0072] Example 3

[0073] Preparation of liquid metal: First, weigh Ga / In / Sn in a ratio of 68:22:10. Mix 6.7962g of Ga and 2.2078g of In at 600rpm for 20 minutes under a 70℃ water bath heating condition. Then add 0.9976g of Sn and continue mixing at 600rpm for 40 minutes under a 70℃ water bath heating condition. Next, prepare a 1mol / L NaOH solution and add about 10mL of NaOH solution to the above metal mixture. Sonicate at 200W for 5 minutes to obtain liquid metal.

[0074] Modification of nano-TiO2: First, 0.5004 g of nano-TiO2 with a particle size of 200 nm was added to 15 mL of cyclohexane and ultrasonically dispersed for 10 minutes at 200 W and stirred at 600 rpm for 10 minutes to ensure uniform dispersion. Then, 0.0052 g of oleic acid (1 wt% of nano-TiO2) was added, and the mixture was stirred at 600 rpm for 2 hours in a 60 °C water bath. Finally, 150 mL of anhydrous ethanol was added dropwise while stirring at 400 rpm to ensure that the volume ratio of cyclohexane to anhydrous ethanol was 1:10. The mixture was allowed to stand, filtered, and allowed to evaporate naturally to obtain the modified nano-TiO2.

[0075] Preparation of metal fire extinguishing agent: 0.4692g of modified nano-TiO2 was added to 20mL of anhydrous ethanol and stirred at 600rpm for 20 minutes. Then, 0.02470g of liquid metal was added to ensure that the mass percentage of liquid metal in modified nano-TiO2 was 5%. The mixture was stirred at 600rpm for 2 hours, accompanied by 200W sonication three times for 5 minutes each time. After drying, a metal fire extinguishing agent with a modified nano-TiO2@liquid metal core-shell structure was obtained.

[0076] Example 4

[0077] Preparation of liquid metal: First, weigh Ga / In / Sn in a ratio of 68:22:10. Mix 6.7962g of Ga and 2.2078g of In at 600rpm for 20 minutes under a 70℃ water bath heating condition. Then add 0.9976g of Sn and continue mixing at 600rpm for 40 minutes under a 70℃ water bath heating condition. Next, prepare a 1mol / L NaOH solution and add about 10mL of NaOH solution to the above metal mixture. Sonicate at 200W for 5 minutes to obtain liquid metal.

[0078] Modification of nano-TiO2: First, 0.4999g of nano-TiO2 with a particle size of 200nm was added to 15mL of cyclohexane and ultrasonically dispersed for 10 minutes at 200W and stirred at 600rpm for 10 minutes to ensure uniform dispersion. Then, 0.0152g of oleic acid (3wt% of nano-TiO2) was added, and the mixture was stirred at 600rpm for 2 hours in a 60℃ water bath. Finally, 150mL of anhydrous ethanol was added dropwise while stirring at 400rpm to ensure that the volume ratio of cyclohexane to anhydrous ethanol was 1:10. The mixture was allowed to stand, filtered, and allowed to evaporate naturally to obtain the modified nano-TiO2.

[0079] Preparation of metal fire extinguishing agent: 0.4578g of modified nano-TiO2 was added to 20mL of anhydrous ethanol and stirred at 600rpm for 20 minutes. Then, 0.0045g of liquid metal was added to ensure that the mass percentage of liquid metal in modified nano-TiO2 was 1%. The mixture was stirred at 600rpm for 2 hours, accompanied by 200W sonication three times for 5 minutes each time. After drying, a metal fire extinguishing agent with a modified nano-TiO2@liquid metal core-shell structure was obtained.

[0080] Example 5

[0081] Preparation of liquid metal: First, weigh Ga / In / Sn in a ratio of 68:22:10. Mix 6.7962g of Ga and 2.2078g of In at 600rpm for 20 minutes under a 70℃ water bath heating condition. Then add 0.9976g of Sn and continue mixing at 600rpm for 40 minutes under a 70℃ water bath heating condition. Next, prepare a 1mol / L NaOH solution and add about 10mL of NaOH solution to the above metal mixture. Sonicate at 200W for 5 minutes to obtain liquid metal.

[0082] Modification of nano-TiO2: First, 0.4993g of nano-TiO2 with a particle size of 200nm was added to 15mL of cyclohexane and ultrasonically dispersed for 10 minutes at 200W and stirred at 600rpm for 10 minutes to ensure uniform dispersion. Then, 0.0155g of oleic acid (3wt% of nano-TiO2) was added, and the mixture was stirred at 600rpm for 2 hours in a 60℃ water bath. Finally, 150mL of anhydrous ethanol was added dropwise while stirring at 400rpm to ensure that the volume ratio of cyclohexane to anhydrous ethanol was 1:10. The mixture was allowed to stand, filtered, and allowed to evaporate naturally to obtain the modified nano-TiO2.

[0083] Preparation of metal fire extinguishing agent: 0.4635g of modified nano-TiO2 was added to 20mL of anhydrous ethanol and stirred at 600rpm for 20 minutes. Then, 0.0142g of liquid metal was added to ensure that the mass percentage of liquid metal in modified nano-TiO2 was 3%. The mixture was stirred at 600rpm for 2 hours, accompanied by 200W sonication three times for 5 minutes each time. After drying, a metal fire extinguishing agent with a modified nano-TiO2@liquid metal core-shell structure was obtained.

[0084] Example 6

[0085] Preparation of liquid metal: First, weigh Ga / In / Sn in a ratio of 68:22:10. Mix 6.7962g of Ga and 2.2078g of In at 600rpm for 20 minutes under a 70℃ water bath heating condition. Then add 0.9976g of Sn and continue mixing at 60rpm for 40 minutes under a 70℃ water bath heating condition. Next, prepare a 1mol / L NaOH solution and add about 10mL of NaOH solution to the above metal mixture. Sonicate at 200W for 5 minutes to obtain liquid metal.

[0086] Modification of nano-TiO2: First, 0.4999g of nano-TiO2 with a particle size of 200nm was added to 15mL of cyclohexane and ultrasonically dispersed for 10 minutes at 200W and stirred at 600rpm for 10 minutes to ensure uniform dispersion. Then, 0.0155g of oleic acid (3wt% of nano-TiO2) was added, and the mixture was stirred at 600rpm for 2 hours in a 60℃ water bath. Finally, 150mL of anhydrous ethanol was added dropwise while stirring at 400rpm to ensure that the volume ratio of cyclohexane to anhydrous ethanol was 1:10. The mixture was allowed to stand, filtered, and allowed to evaporate naturally to obtain the modified nano-TiO2.

[0087] Preparation of metal fire extinguishing agent: 0.4594g of modified nano-TiO2 was added to 20mL of anhydrous ethanol and stirred at 600rpm for 20 minutes. Then, 0.0246g of liquid metal was added to ensure that the mass percentage of liquid metal in modified nano-TiO2 was 5%. The mixture was stirred at 600rpm for 2 hours, accompanied by 200W sonication three times for 5 minutes each time. After drying, a metal fire extinguishing agent with a modified nano-TiO2@liquid metal core-shell structure was obtained.

[0088] Example 7

[0089] Preparation of liquid metal: First, weigh Ga / In / Sn in a ratio of 68:22:10. Mix 6.7962g of Ga and 2.2078g of In at 600rpm for 20 minutes under a 70℃ water bath heating condition. Then add 0.9976g of Sn and continue mixing at 600rpm for 40 minutes under a 70℃ water bath heating condition. Next, prepare a 1mol / L NaOH solution and add about 10mL of NaOH solution to the above metal mixture. Sonicate at 200W for 5 minutes to obtain liquid metal.

[0090] Modification of nano-TiO2: First, 0.5003g of nano-TiO2 with a particle size of 200nm was added to 15mL of cyclohexane and ultrasonically dispersed for 10 minutes at 200W and stirred at 600rpm for 10 minutes to ensure uniform dispersion. Then, 0.0262g of oleic acid (5wt% of nano-TiO2) was added, and the mixture was stirred at 600rpm for 2 hours in a 60℃ water bath. Finally, 150mL of anhydrous ethanol was added dropwise while stirring at 400rpm to ensure that the volume ratio of cyclohexane to anhydrous ethanol was 1:10. The mixture was allowed to stand, filtered, and allowed to evaporate naturally to obtain the modified nano-TiO2.

[0091] Preparation of metal fire extinguishing agent: 0.4623g of modified nano-TiO2 was added to 20mL of anhydrous ethanol and stirred at 600rpm for 20 minutes. Then, 0.0047g of liquid metal was added to ensure that the mass percentage of liquid metal in modified nano-TiO2 was 1%. The mixture was stirred at 600rpm for 2 hours, accompanied by 200W sonication three times for 5 minutes each time. After drying, a metal fire extinguishing agent with a modified nano-TiO2@liquid metal core-shell structure was obtained.

[0092] Example 8

[0093] Preparation of liquid metal: First, weigh Ga / In / Sn in a ratio of 68:22:10. Mix 6.7962g of Ga and 2.2078g of In at 600rpm for 20 minutes under a 70℃ water bath heating condition. Then add 0.9976g of Sn and continue mixing at 600rpm for 40 minutes under a 70℃ water bath heating condition. Next, prepare a 1mol / L NaOH solution and add about 10mL of NaOH solution to the above metal mixture. Sonicate at 200W for 5 minutes to obtain liquid metal.

[0094] Modification of nano-TiO2: First, 0.5000g of nano-TiO2 with a particle size of 200nm was added to 15mL of cyclohexane and ultrasonically dispersed for 10 minutes at 200W and stirred at 600rpm for 10 minutes to ensure uniform dispersion. Then, 0.0259g of oleic acid (5wt% of nano-TiO2) was added, and the mixture was stirred at 600rpm for 2 hours in a 60℃ water bath. Finally, 150mL of anhydrous ethanol was added dropwise while stirring at 400rpm to ensure that the volume ratio of cyclohexane to anhydrous ethanol was 1:10. The mixture was allowed to stand, filtered, and allowed to evaporate naturally to obtain the modified nano-TiO2.

[0095] Preparation of metal fire extinguishing agent: 0.4614 g of modified nano TiO2 was added to 20 mL of anhydrous ethanol and stirred at 600 rpm for 20 minutes. Then, 0.0145 g of liquid metal was added to ensure that the mass percentage of liquid metal in modified nano TiO2 was 3%. The mixture was stirred at 600 rpm for 2 hours, accompanied by 200 W sonication three times for 5 minutes each time. After drying, a metal fire extinguishing agent with a modified nano TiO2@liquid metal core-shell structure was obtained.

[0096] Example 9

[0097] Preparation of liquid metal: First, weigh Ga / In / Sn in a ratio of 68:22:10. Mix 6.7962g of Ga and 2.2078g of In at 600rpm for 20 minutes under a 70℃ water bath heating condition. Then add 0.9976g of Sn and continue mixing at 600rpm for 40 minutes under a 70℃ water bath heating condition. Next, prepare a 1mol / L NaOH solution and add about 10mL of NaOH solution to the above metal mixture. Sonicate at 200W for 5 minutes to obtain liquid metal.

[0098] Modification of nano-TiO2: First, 0.5001g of nano-TiO2 with a particle size of 200nm was added to 15mL of cyclohexane and ultrasonically dispersed for 10 minutes at 200W and stirred at 600rpm for 10 minutes to ensure uniform dispersion. Then, 0.0262g of oleic acid (5wt% of nano-TiO2) was added, and the mixture was stirred at 600rpm for 2 hours in a 60℃ water bath. Finally, 150mL of anhydrous ethanol was added dropwise while stirring at 400rpm to ensure that the volume ratio of cyclohexane to anhydrous ethanol was 1:10. The mixture was allowed to stand, filtered, and allowed to evaporate naturally to obtain the modified nano-TiO2.

[0099] Preparation of metal fire extinguishing agent: 0.4665g of modified nano-TiO2 was added to 20mL of anhydrous ethanol and stirred at 600rpm for 20 minutes. Then, 0.0253g of liquid metal was added to ensure that the mass percentage of liquid metal in modified nano-TiO2 was 5%. The mixture was stirred at 600rpm for 2 hours, accompanied by 200W sonication three times for 5 minutes each time. After drying, a metal fire extinguishing agent with a modified nano-TiO2@liquid metal core-shell structure was obtained.

[0100] Example 10

[0101] Preparation of liquid metal: First, weigh Ga / In / Sn in a ratio of 68:22:10. Mix 6.7962g of Ga and 2.2078g of In at 600rpm for 20 minutes under a 70℃ water bath heating condition. Then add 0.9976g of Sn and continue mixing at 600rpm for 40 minutes under a 70℃ water bath heating condition. Next, prepare a 1mol / L NaOH solution and add about 10mL of NaOH solution to the above metal mixture. Sonicate at 200W for 5 minutes to obtain liquid metal.

[0102] Modification of nano-TiO2: First, 0.0097g of F2311 and 4mL of DMF were stirred at 600rpm for 1 hour. Then, 0.4997g of nano-TiO2 with a particle size of 200nm was added to ensure that the mass percentage of F2311 in the nano-TiO2 was 2%. After sonication at 200W for 10 minutes, the mixture was stirred at 600rpm in a 60℃ water bath for 2 hours. Finally, 60mL of anhydrous ethanol was added dropwise while stirring at 400rpm to ensure that the volume ratio of F2311 to anhydrous ethanol was 1:15. The mixture was allowed to stand, filtered, and allowed to evaporate naturally to obtain the modified nano-TiO2.

[0103] Preparation of metal fire extinguishing agent: 0.5584g of modified nano-TiO2 was added to 20mL of anhydrous ethanol and stirred at 600rpm for 20 minutes. Then, 0.0055g of liquid metal was added to ensure that the mass percentage of liquid metal in modified nano-TiO2 was 1%. The mixture was stirred at 600rpm for 2 hours, accompanied by 200W sonication three times for 5 minutes each time. After drying, a metal fire extinguishing agent with a modified nano-TiO2@liquid metal core-shell structure was obtained.

[0104] Example 11

[0105] Preparation of liquid metal: First, weigh Ga / In / Sn in a ratio of 68:22:10. Mix 6.7962g of Ga and 2.2078g of In at 600rpm for 20 minutes under a 70℃ water bath heating condition. Then add 0.9976g of Sn and continue mixing at 600rpm for 40 minutes under a 70℃ water bath heating condition. Next, prepare a 1mol / L NaOH solution and add about 10mL of NaOH solution to the above metal mixture. Sonicate at 200W for 5 minutes to obtain liquid metal.

[0106] Modification of nano-TiO2: First, 0.0103g of F2311 and 4mL of DMF were stirred at 600rpm for 1 hour. Then, 0.5003g of nano-TiO2 with a particle size of 200nm was added to ensure that the mass percentage of F2311 in the nano-TiO2 was 2%. After sonication at 200W for 10 minutes, the mixture was stirred at 600rpm in a 60℃ water bath for 2 hours. Finally, 60mL of anhydrous ethanol was added dropwise while stirring at 400rpm to ensure that the volume ratio of F2311 to anhydrous ethanol was 1:15. The mixture was allowed to stand, filtered, and allowed to evaporate naturally to obtain the modified nano-TiO2.

[0107] Preparation of metal fire extinguishing agent: 0.5624g of modified nano-TiO2 was added to 20mL of anhydrous ethanol and stirred at 600rpm for 20 minutes. Then, 0.0185g of liquid metal was added to ensure that the mass percentage of liquid metal in modified nano-TiO2 was 3%. The mixture was stirred at 600rpm for 2 hours, accompanied by 200W sonication three times for 5 minutes each time. After drying, a metal fire extinguishing agent with a modified nano-TiO2@liquid metal core-shell structure was obtained.

[0108] Example 12

[0109] Preparation of liquid metal: First, weigh Ga / In / Sn in a ratio of 68:22:10. Mix 6.7962g of Ga and 2.2078g of In at 600rpm for 20 minutes under a 70℃ water bath heating condition. Then add 0.9976g of Sn and continue mixing at 600rpm for 40 minutes under a 70℃ water bath heating condition. Next, prepare a 1mol / L NaOH solution and add about 10mL of NaOH solution to the above metal mixture. Sonicate at 200W for 5 minutes to obtain liquid metal.

[0110] Modification of nano-TiO2: First, 0.0096g of F2311 and 4mL of DMF were stirred at 600rpm for 1 hour. Then, 0.5000g of nano-TiO2 with a particle size of 200nm was added to ensure that the mass percentage of F2311 in the nano-TiO2 was 2%. After sonication at 200W for 10 minutes, the mixture was stirred at 600rpm in a 60℃ water bath for 2 hours. Finally, 60mL of anhydrous ethanol was added dropwise while stirring at 400rpm to ensure that the volume ratio of F2311 to anhydrous ethanol was 1:15. The mixture was allowed to stand, filtered, and allowed to evaporate naturally to obtain the modified nano-TiO2.

[0111] Preparation of metal fire extinguishing agent: 0.5498g of modified nano-TiO2 was added to 20mL of anhydrous ethanol and stirred at 600rpm for 20 minutes. Then, 0.0291g of liquid metal was added to ensure that the mass percentage of liquid metal in modified nano-TiO2 was 5%. The mixture was stirred at 600rpm for 2 hours, accompanied by 200W sonication three times for 5 minutes each time. After drying, a metal fire extinguishing agent with a modified nano-TiO2@liquid metal core-shell structure was obtained.

[0112] Comparative Example 1

[0113] Preparation of liquid metal: First, weigh Ga / In / Sn in a ratio of 68:22:10. Mix 6.7962g of Ga and 2.2078g of In at 600rpm for 20 minutes under a 70℃ water bath heating condition. Then add 0.9976g of Sn and continue mixing at 600rpm for 40 minutes under a 70℃ water bath heating condition. Next, prepare a 1mol / L NaOH solution and add about 10mL of NaOH solution to the above metal mixture. Sonicate at 200W for 5 minutes to obtain liquid metal.

[0114] Preparation of metal fire extinguishing agent: 0.5005g of nano-TiO2 with a particle size of 200nm was added to 20mL of anhydrous ethanol and stirred at 600rpm for 20 minutes. Then, 0.0155g of liquid metal was added to ensure that the mass percentage of liquid metal in nano-TiO2 was 3%. The mixture was stirred at 600rpm for 2 hours, accompanied by 200W sonication 3 times for 5 minutes each time. After drying, the nano-TiO2@liquid metal core-shell structure composite could not be obtained.

[0115] Comparative Example 2

[0116] The difference between Comparative Example 2 and Example 4 is that no liquid metal coating was performed, while the other conditions were the same as in Example 4, that is, 3wt% oleic acid modified nano-TiO2 was directly used as the fire extinguishing agent.

[0117] Test case

[0118] The fire extinguishing performance of the fire extinguishing agents prepared in each embodiment and each comparative example was tested. The test methods and test conditions are as follows:

[0119] A magnesium strip with dimensions of 120mm×1.3mm×0.2mm was laid flat, and 5g of the prepared extinguishing agent was evenly spread on the magnesium strip. Ni-Cr wire was used for ignition. The length of the remaining magnesium strip after combustion was measured. Each sample was tested 3 times, and the average value was calculated. The longer the remaining unburned length, the better the extinguishing effect. The test results are shown in Table 1.

[0120] Table 1

[0121]

[0122]

[0123] As can be seen from the data in Table 1, the metal fire extinguishing agent prepared by the method of the present invention has a good fire extinguishing effect; Figure 2 The diagram shows the fire extinguishing effect of the fire extinguishing agent prepared in Example 5 of this invention. After covering the fire extinguishing agent prepared in this example, after the 12cm magnesium strip burns, the remaining unburned magnesium strip can reach 10cm in length, while the magnesium strip (12cm) without the fire extinguishing agent is completely burned, showing excellent fire extinguishing effect.

[0124] Although the present invention has been illustrated and described with specific embodiments, it should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and scope of the present invention; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention; therefore, this means that all such substitutions and modifications that fall within the scope of the present invention are included in the appended claims.

Claims

1. A metal fire extinguishing agent, characterized in that, It includes modified nano-TiO2 and at least partially coated with liquid metal on the outer surface of the modified nano-TiO2; the liquid metal includes an alloy of one or more of gallium, indium, and tin. The modified nano-TiO2 includes nano-TiO2 and a surface modifier that at least partially coats the outer surface of the nano-TiO2, wherein the nano-TiO2 has anatase crystal form; the surface modifier includes oleic acid and / or F2311.

2. The metal fire extinguishing agent according to claim 1, characterized in that, The particle size of the nano-TiO2 is 20-500 nm.

3. The method for preparing the metal fire extinguishing agent according to claim 1 or 2, characterized in that, Includes the following steps: The metal fire extinguishing agent is obtained by coating liquid metal onto the surface of modified nano-TiO2.

4. The method for preparing the metal fire extinguishing agent according to claim 3, characterized in that, The method for coating liquid metal includes the following steps: The modified nano-TiO2 is dispersed in a first solvent, the liquid metal is added, and after mixing and drying, the product is obtained.

5. The method for preparing the metal fire extinguishing agent according to claim 4, characterized in that, It contains at least one of the following features: (1) The liquid metal accounts for 1%-10% of the mass percentage of the modified nano-TiO2; (2) The first solvent includes ethanol.

6. The method for preparing the metal fire extinguishing agent according to claim 3, characterized in that, The preparation method of the modified nano-TiO2 includes the following steps: The nano-TiO2 and the surface modifier are dispersed in a second solvent. After the reaction is complete, a TiO2-modifier dispersion is obtained. The TiO2-modifier dispersion is then dropped into a non-solvent under stirring. After standing, filtering, and drying, the modified nano-TiO2 is obtained.

7. The method for preparing the metal fire extinguishing agent according to claim 6, characterized in that, It contains at least one of the following features: (1) When the surface modifier is oleic acid, the second solvent includes cyclohexane and / or n-hexane; when the surface modifier is F2311, the second solvent includes DMF and / or DMAc. (2) The surface modifier accounts for 1%-5% of the mass of the nano-TiO2; (3) The reaction temperature is 50-60℃, and the reaction time is 1-3h; (4) The non-solvents include ethanol and / or methanol; (5) The volume ratio of the second solvent to the non-solvent is 1:2 to 1:30; (6) The rotation speed when the TiO2-modifier dispersion is dropped into the non-solvent is 400-1200 rpm.

8. The application of the metal fire extinguishing agent according to claim 1 or 2 in extinguishing metal fires.

Citation Information

Patent Citations

  • Metal surface cross-linked protective film

    CN107674479A

  • Preparation method of flame-retardant composition based on titanium dioxide

    CN107952201A